EXPERIMENTAL STUDY OF INTEGRATION FEATURES OF POROUS PERMEABLE AND MESH TITANIUM NICKELIDE IN VIVO - M.SH. MIRZOEV; M.N. SHAKIROV; E.D. POROKHOVA; R.N. DZHONIBEKOVA (Avicenna Tajik State Medical University, 2020)
Objective: Morphological assessment of the integration features of the combined use of porous permeable and textile mesh titanium nickelide with bone structures of the recipient zone. Methods: The study was carried out on 20 Chinchilla rabbits of both sexes at the age of 1-1.5 years with a bodyweight of 2500-4000 g. In animals, the artificial defect was created in one of the areas of the lower jaw, where a porous permeable titanium nickelide was installed, wrapped in a textile mesh version of it was installed. Animals were removed from the experiment for 30, 90, 180, and 360 days of research via intraperitoneal injection of mortal dose 1% solution thiopental sodium. The material for histological research was fixed in 10% buffered formalin during 12 hours after then washed with water and decalcified. The prepared sections were stained with hematoxylin-eosin. Microscopic examination of the stained preparations and photography were carried out using a light microscope Axioscope 40 (Zeiss, Germany) via a digital camera (Canon, Japan). Results: Studies have shown that with the combined use of porous permeable and textile mesh titanium nickelide, the artificially created defects of the mandibula between both contacting surfaces are formed directly, which leads to stable fixing. The porous structure of the material, its hysteresis behavior with organism tissues, provides widespread regeneration of cells and formed a homogeneous mature bone tissue bone tissue, both in the pores and around the structure. Conclusion: These and other facts indicate the high integration properties of the material that is investigated, which ensures optimal growth and population of osteogenic cells in the vicinity of defective bone areas in a growing organism.